CNS efficacy parameters of combination antiretroviral therapy in chronic HIV infection: A multi-voxel magnetic resonance spectroscopy study - Brkic, Snezana; Veres, Benjamin; Thurnher, Majda M.; Boban, Jasmina; Radovanovic, Bojan; Tomic, Slavica; Kozic, Dusko (Frontiers in Neurology, 2023)
The aim of this study was to determine correlations of combination antiretroviral therapy (cART) efficacy parameters in central nervous system (CNS) with neurometabolic profile on magnetic resonance spectroscopy (MRS) in virally-suppressed, neurologically asymptomatic HIV+ individuals. Thirty-two HIV+ individuals on stable cART, average age 41.97±10.12 years, with available clinical data, CNS penetration effectiveness (CPE) and monocyte efficacy (ME) scores, underwent multi-voxel MRS. Parameters of neuronal number/function (NAA/Cr), membrane turnover (Cho/Cr) and glial proliferation (mI/Cr) were analyzed in supratentorial white and grey matter. Correlations of CPE and ME with neurometabolite ratios were performed using Pearson's correlation test. Statistical significance was set at p<0.05. A strong positive correlation was observed between Cho/Cr and CPE in left parietal subcortical white matter (r=0.577, p= 0.001). A strong positive correlation between NAA/Cr and ME were obtained in left (r=0.521, p=0.003) and right (r=0.494, p=0.005) posterior cingulate. A strong negative correlation between ME and Cho/Cr ratios was observed in right frontal deep white matter (r=-0.569, p=0.001). Indices designed to assess cART efficacy in CNS failed to present significant correlations with neurometabolic profile obtained using MRS. There is an urge to define more potent non-invasive tools for neuroinflammation assessment, given the prolonged life expectancy in HIV+ population.